Mutation-induced conformational changes and energetics for binding of FMN ligand in Flavin Mononucleotide riboswitch by molecular dynamics simulations - Wakchaure, Padmaja D. (Array, 2019)
Riboswitches are the type of regulatory elements present in the untranslated region of mRNA and specifically bind to the natural ligand to regulate gene expression. This binding specificity can be affected by even single point mutation incorporated in the core of the riboswitch. In this work, we have examined the mutations at the binding site residue in Flavin Mononucleotide (FMN) riboswitch structure with 30ns molecular dynamics simulations. The interaction of ligand (FMN) with riboswitch has been characterized using root mean square deviation, hydrogen bonding analysis, and the calculated binding affinities. Mutation at A48G and G62U show the enhanced binding energy however, the mutation at A85G, are energetically unfavorable compared to the wild type. This work gives valuable insight into the structures and energetics of the mutated FMN riboswitch to design new hits for biological applications.